THE IMPACT OF DIGITAL TOOLS ON DEVELOPING SPEAKING SKILLS OF EFL LEARNERS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This study argues that integrating digital tools into English as Foreign Language (EFL) speaking instruction significantly enhances learners’ communicative competence by improving their fluency, pronunciation, confidence, and motivation. Through the use of platforms such as Zoom, Flipgrid, and Duolingo, digital environments create expanded opportunities for authentic interaction, learner autonomy, and self-regulated practice beyond the traditional classroom.